The integration of Total Quality Management (TQM) and Theory Of Constraints (TOC) implementation in Malaysian automotive suppliers - Zadry, Hilma Raimona (2005)
The automotive industry is one of the most important and strategic industries in the Malaysian manufacturing sector. It supports a large number of Small and Medium Enterprises (SMEs). The Malaysian automotive industry, especially the suppliers, must be able to stay competitive and be in business. In order to be able to achieve the above goals, suppliers should apply Total Quality Management (TQM) to improve the quality of products and services in satisfying the customers. Theory of Constraints (TOC) is a systems methodology that has been developed to assist people and organizations to think about their problems, develop breakthrough solutions and implement those solutions successfully. This study has attempted to integrate TQM and TOC in enhancing the implementation of TQM. There has not been any well research about the integration of TQM and TOC implementation, especially in Malaysia. So, it is hoped that this study can help Malaysian SMEs, especially automotive suppliers, to implement TQM better. Survey methodology and case study have been conducted to determine the extent of TQM and TOC implementation in Malaysian automotive suppliers. The TOC Thinking Process (TP) tools were used to analyze data from survey and case study to find out and reduce some of the problems of TQM implementation in Malaysian automotive suppliers. It was found that Malaysian automotive suppliers have achieved quite a high level of their quality implementation programs, although most of them are still in the early stage of implementing TQM. There were also still problems in their implementation of TQM. By using TOC TP tools, it was found that the core problem of the TQM implementation in Malaysian automotive suppliers was lack of management leadership and commitment to TQM. The main contribution of this study is a proposed framework for the integration of TQM and TOC in assisting companies for the implementation of TQM.